Problem-Based Learning Application To Improve Students' Ability Editing - Nurlina, Laily; Fauzan, Akhmad (Syntax Literate, 2021)
This research aims to know the implementation PBL based on technology on boosting students’ editing competence in University of Muhammadiyah Purwokerto. The advancement of technology made changing in students’ habit rapidly. They rarely reading books or newspaper instead of cellular. Everyone can write if they read a lot of information. When the students can not write, they got difficulty to edit text. That’s why it was important to use technology on editing subject in semester 5 PBSI-UMP. The population was 79 students in two classes by random sampling class A as experiment class. The method used experiment by mixed quantitative and qualitative data. The instruments are questionnaire and test. The calculation showed sig. Levene’s test for Equality of Variances 0.264>0.05 means hypothesis was accepted. So, PBL based technology effectively improved students’ editing competence.